The Efficacy and Safety of the mTOR Signaling Pathway Activator, MHY1485, for in vitro Activation of Human Ovarian Tissue - Wu, Shuang; Wang, Yining; Ding, Haixiang; Sun, Ningxia; Liu, Yan; Wang, Liang; Sheng, Fei; Zhang, Honghong; Yang, Fu; Li, Wen (Frontiers in Genetics, 2021)
Background Premature ovarian insufficiency (POI) is characterized by abnormal ovarian function before the age of 40. POI showed that primordial follicles developed in disorder. mTOR signaling plays a vital role in the process of follicle development. It has been verified that the mTOR signaling pathway activator, MHY1485, can promote primordial follicle development in mice. We considered that MHY1485 would be a promising fertility preservation method for POI patients. Methods The fragmented ovarian tissues of normal woman was cultured with activator MHY1485 in vitro, and then the control and activated ovaries were transplanted into the kidney capsules of ovariectomized mice. We then used the Infinium Human Methylation EPIC BeadChip to verify the DNA methylation level of ovarian tissues, thus exploring the effectiveness of them. Results MHY1485 stimulated mTOR, S6K1, and rpS6 phosphorylation. Cultured with MHY1485, ovarian weights increased and endocrine function was restored. The number of growing follicles was increased. The in vitro activation process did not induce histological changes or abnormal DNA methylation occurrence. Conclusion MHY1485 for in vitro activation (IVA) is effective for ovarian rejuvenation and is a potential therapeutic treatment for POI patients.